Cross: A generic framework for system integration and its adaption in hospitals. (26th February 2022) - Sun, Wen‐Lin; Huang, Yu‐Lun
Abstract: Advances in healthcare systems require faster data transmission between medical instruments and hospital information systems (HISs) and cloud migration for better computing capability and scalability. Old medical instruments should be integrated with modern HISs to provide real‐time examination service to patients. Still, such integration carries some problems, especially when novel services are involved, such as real‐time fall detection and mobile healthcare. Some hospitals have formulated standard operating procedures (SOPs) in response, requiring the electronic health record generated by an old instrument to be manually converted and uploaded to the HIS by medical personnel. However, such SOPs may compromise the real‐time performance and increase medical personnel workload and complexity. Thus, this article proposes a framework named Cross, which comprises an embedded bridging module, CrossBridger, and a server‐side software program, CrossServer, to integrate old instruments into a modern HIS using an edge computing paradigm. With Cross, users can solve system integration problems and deploy more protective strategies in existing HISs to fulfill the demands of novel services relatively cheaply. Based on the proposed framework, we implement a solution that can automate most existing SOPs and lighten the workload of medical personnel so that they can provide better care and service to patients. We summarize the practical experience of the implementation based on the solution. As a case study, we deploy the implementation to a real‐world hospital to demonstrate the feasibility of Cross. Furthermore, we evaluate Cross's efficacy under various network statuses in three experiments.